2001
DOI: 10.1046/j.1365-3156.2001.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

The phenomenon of treatment failures in Human African Trypanosomiasis

Abstract: SummaryTreatment of Human African Trypanosomiasis (HAT or sleeping sickness) relies on a few drugs which are old, toxic and expensive. The most important drug for the treatment of second stage infection is melarsoprol. During the last 50 years treatment failures with melarsoprol were not a major problem in Trypanosoma brucei gambiense patients. Commonly a relapse rate of 5±8% was reported, but in recent years it has increased dramatically in some important foci of T. b. gambiense sleeping sickness. Treatment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
134
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(137 citation statements)
references
References 24 publications
3
134
0
Order By: Relevance
“…In addition, conflicts and insecurity constrained disease control interventions (130,131). An analysis of the period showed that cases of HAT occurred significantly more often in settings with political turmoil and internationalized civil war, with a 10-year interval between onset of conflict and peak prevalence (132). By the 1990s, epidemic disease had returned to central Africa (113,130,133,134).…”
Section: Gambiense Human African Trypanosomiasismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, conflicts and insecurity constrained disease control interventions (130,131). An analysis of the period showed that cases of HAT occurred significantly more often in settings with political turmoil and internationalized civil war, with a 10-year interval between onset of conflict and peak prevalence (132). By the 1990s, epidemic disease had returned to central Africa (113,130,133,134).…”
Section: Gambiense Human African Trypanosomiasismentioning
confidence: 99%
“…So far, relatively little progress has been made in the screening of rhodesiense HAT. However, suitable antigens for antibody detection and plasma biomarkers for T. b. rhodesiense infection are being searched for (24,131,132). If successful, these may allow development of rapid diagnostic tests for rhodesiense HAT as well.…”
Section: New Developments and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is an urgent need for new molecules against sleeping sickness which are safe, effective, cheap and easy-to-administer and for new leads with novel mechanisms of action. [8][9][10][11] Nature with its numerous plants, microorganisms and marine organisms is a potential source of such new drugs since it contains a countless quantity of molecules with a great variety of structures and pharmacological activities. 12 Throughout the ages, mineral, plant and animal products have been the main sources of medicines for man.…”
Section: Introductionmentioning
confidence: 99%
“…However, drug resistance in trypanosomes is increasing and treatment failures are becoming more common. 4,5 Therefore, there is an urgent need for new antitrypanosomal drugs that are more effective and safer, especially those that have novel structures and mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%